Faktor-Faktor Yang Mempengaruhi Kinerja Bank (Studi Empirik pada Bank Syariah di Cirebon) - Surono Surono (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2012)
Purpose of this study to obtain empirical evidence and find the clarity of the phenomenon as well as conclusions about the effect of organization culture, managerial competency and organization environment factor on bank performance. This thesis is expected to contribute to the development of management accounting science.The primary data received from manager of Syariah Bank in Cirebon, collected by mail survey. 33 questionnaires were send to bank Syariah managers and 30 respondents give their perception with respond rate 91% the data analyze by using multiple regression. The result showed that organization culture, managerial competency and organization environment have a positive effect to bank performance.